The Dynamic Link of Electricity Consumption, Internet Access and Economic Growth in 33 Provinces of Indonesia - Amaluddin, Amaluddin (International Journal of Energy Economics and Policy, 2020)
The dynamic causal relationship between electricity consumption, internet access, and economic growth has been widely studied in many countries both developed and developing countries. However, the debate about these issues continues due to the empirical finding results are mixed and have not reached a consensus. This study highlights the pattern of dynamic causal linkage between electricity consumption, internet access, and economic growth both in the short-term and long-run by employing PVECM, and panel DOLS. The type of data used is secondary data in the panel data set of 33 provinces of Indonesia during the period 2009-2018. All data were collected from the Central Bureau of Statistics of Indonesia (BPS) and the Ministry of Energy and Mineral Resources. The empirical finding of this study found strong evidence to support the long-run feedback hypothesis in the case of the energy-growth nexus, energy-ICT nexus, and ICT-growth nexus. The proponents of the feedback hypothesis argued that increasing energy consumption favorably affects ICT usage and economic growth acceleration, conversely, the acceleration of the high economic growth and the improvement of ICT require more energy consumption. Nevertheless, in the short-run, this study only found the empirical result to corroborate the neutrality hypothesis. Keywords: Electricity; Internet, Economic Growth, Causality, PVECM, Panel DOLS JEL Classifications: O33, O47, Q43 DOI: https://doi.org/10.32479/ijeep.9249